2020
DOI: 10.26504/sustat94
|View full text |Cite
|
Sign up to set email alerts
|

The implications of the COVID-19 pandemic for policy in relation to children and young people: a research review

Abstract: The mission of the Economic and Social Research Institute is to advance evidencebased policymaking that supports economic sustainability and social progress in Ireland. ESRI researchers apply the highest standards of academic excellence to challenges facing policymakers, focusing on 12 areas of critical importance to 21st Century Ireland. The Institute was founded in 1960 by a group of senior civil servants led by Dr T. K. Whitaker, who identified the need for independent and in-depth research analysis to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 52 publications
2
49
0
Order By: Relevance
“…Our findings highlight that the move to remote schooling appears to have further compounded existing inequalities with regards to material, social and cultural resources. Access to appropriate devices, space and other material resources emerged as an issue for many students, and was well-documented as being particularly problematic in DEIS schools (Darmody, Smyth, and Russell 2020;Devitt et al 2020). This paper however, also highlighted that teachers considered these material factors as less impactful than barriers more generally associated with social and cultural resources (interest and home support).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings highlight that the move to remote schooling appears to have further compounded existing inequalities with regards to material, social and cultural resources. Access to appropriate devices, space and other material resources emerged as an issue for many students, and was well-documented as being particularly problematic in DEIS schools (Darmody, Smyth, and Russell 2020;Devitt et al 2020). This paper however, also highlighted that teachers considered these material factors as less impactful than barriers more generally associated with social and cultural resources (interest and home support).…”
Section: Discussionmentioning
confidence: 99%
“…The challenges presented by the COVID-19 school closures have been the topic of educational research both in Ireland and internationally (Darmody, Smyth, and Russell 2020;Eyles, Gibbons, and Montebruno Bondi 2020). With the sudden change in education from in-school to remote learning, early research findings showed clear challenges for continuity of learning and school engagement for students in general, but especially for students who experienced educational disadvantage (Devitt et al 2020;Green 2020).…”
Section: Research Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Overall restrictions generally increased between mid-March and mid-April, to the point where only workplaces classified as essential such as supermarkets were allowed to open in around half of 26 EU countries 3 (Darmody et al, 2020). The Irish government initially recommended for employees to work from home where possible, before moving to close all workplaces bar those deemed essential in April and May, due to the increase of cases.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has had substantial repercussions in almost every sphere of human life, including its 'social, cultural, political, educational, psychological, and interpersonal' aspects (Markowska-Manista and Zakrzewska-Olędzka 2020: 93). Many scholars, scientists, and analysts have been conducting studies of the pandemic's influence on various fields, including migration (Sirkeci and Yucesahin 2020), education (Ministertwo Edukacji Narodowej 2020; OECD 2020; UNESCO 2020), and families (Darmody 2020;WHO 2020). Studies with young people and children reveal the impact on the learning/teaching process, children's well-being, and how families function during times of chaos and disorganization caused by restrictions and limitations (Markowska-Manista and Zakrzewska-Olędzka 2020).…”
Section: Introductionmentioning
confidence: 99%